Increased Drug Resistance and Biofilm Formation Ability in ST34-Type Salmonella Typhimurium Exhibiting Multicellular Behavior in China - Chen, Kaifeng; Gao, Yuan; Li, Lili; Zhang, Weixiao; Li, Jiayi; Zhou, Zhouping; He, Haishan; Chen, Zeluan; Liao, Ming; Zhang, Jianmin (Frontiers in Microbiology, 2022)
Salmonella Typhimurium is an important food-borne pathogen. In this paper, multicellular behavior and associated characteristics of S. Typhimurium isolated from human and animal source food were studied. All the S. Typhimurium strains exhibiting multicellular behavior (100%) belonged to the ST34 type. In addition, most of the ST34-type multicellular behavior S. Typhimurium strains had a human origin (69.11%) and 98% of the ST34-type multicellular behavior strains exhibited strong biofilm formation capacity, which was much higher than that of non-multicellular behavior strains (7%, P < 0.01). Antibiotic resistance in ST34-type multicellular behavior strains was significantly higher than in strains with non-multicellular behavior for most conventional drugs (P < 0.05); notably, Polymyxin B (8%) and Imipenem (1%) resistances were also observed in the ST34-type strains. Furthermore, all the ST34-type multicellular behavior strains (100%) exhibited Multiple Drug Resistance (resistance to ≥3antibiotics), which was much higher than that of the non-multicellular behavior strains (P < 0.05). Consistent with the drug-resistant phenotype, the carrying rates of most drug-resistant genes in ST34-type multicellular behavior strains were higher than that those in non-multicellular behavior strains (P < 0.05). Therefore, this study revealed the emergence of a prevalent ST34-type multicellular behavior S. Typhimurium strains with increased biofilm formation ability and drug resistance rate, which poses a threat to public health safety, and highlights the need for comprehensive monitoring of the strains.